2015
DOI: 10.1080/13607863.2015.1060947
|View full text |Cite
|
Sign up to set email alerts
|

Phone behaviour and its relationship to loneliness in older adults

Abstract: Objectives Loneliness and social isolation are two important health outcomes among older adults. Current assessment of these outcomes relies on self-report which is susceptible to bias. This paper reports on the relationship between loneliness and objective measures of isolation using a phone monitoring device. Method Phone monitors were installed in the homes of 26 independent elderly individuals from the ORCATECH Life Laboratory cohort (age 86 ± 4.5, 88% female) and used to monitor the daily phone usage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 44 publications
(38 reference statements)
8
42
1
Order By: Relevance
“…Participants in high-score group receive less incoming calls at any time. Petersen et al (2015) also found that loneliness is tightly associated with incoming but not outgoing calls. Besides, lonely individuals tend to use healthy apps more frequently, which can provide them online and ubiquitous access to health care services, and this finding confirms that lonely people prefer to use health care system ( Geller et al, 1999 ).…”
Section: Discussionmentioning
confidence: 87%
“…Participants in high-score group receive less incoming calls at any time. Petersen et al (2015) also found that loneliness is tightly associated with incoming but not outgoing calls. Besides, lonely individuals tend to use healthy apps more frequently, which can provide them online and ubiquitous access to health care services, and this finding confirms that lonely people prefer to use health care system ( Geller et al, 1999 ).…”
Section: Discussionmentioning
confidence: 87%
“…We were also not able to differentiate between incoming calls and outgoing calls in this study as not all the phone companies we collected logs from stored this information. This was unfortunate as previous work has demonstrated that loneliness is more closely linked to the number of incoming calls than outgoing calls [39]. Future studies on loneliness in older adults should include incoming and outgoing calls separately.…”
Section: Discussionmentioning
confidence: 98%
“…Because loneliness may change in response to many life events and is closely related to social isolation, it may be more timely and informative to identify lonely individuals by tracking changes in the social network or other daily behaviors using unobtrusive monitoring techniques (Kaye et al, 2010; Petersen, Austin, Kaye, Pavel, & Hayes, 2014). For example, tracking call history would enable assessment of social network size and frequency of contact—the two major components of social isolation scales (Petersen, Thielke, Austin, & Kaye, 2015). Other behaviors that may relate to loneliness that can be tracked unobtrusively include time spent outside the home (Petersen et al, 2014; Petersen, Austin, Mattek, & Kaye, 2015), computer use (Amichai-Hamburger & Ben-Artzi, 2003), and sleep quality (Hawkley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%